Complementary strands of CELO virus DNA. - Robinson, A J (1975)
When alkali-denatured DNA from CELO virus (an avian adenovirus) was annealed for 15 min at 37 C in 0.1 M NaCl, 70% of the molecules formed single-stranded circles. This is probably due to base pairing of complementary sequences not more than 110 nucleotides long at the ends of the single strands and implies an inverted terminal repetition in the duplex DNA similar to that reported for the DNA from human adenoviruses. The circular molecules had a uniform length that was approximately the same as that of linear single-stranded molecules. The complementary strands of CELO virus DNA were separated on a preparative scale, and at least 40% of the heavy strands and 56% of the light strands were found to be intact as judged by the formation of single-stranded circles.